Safety Cultures, Safety Models Taking Stock and Moving Forward - Gilbert, Claude; Journé, Benoît; Laroche, Hervé; Bieder, Corinne; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The objective of this book is to help at-risk organizations to decipher the "safety cloud", and to position themselves in terms of operational decisions and improvement strategies in safety, considering the path already travelled, their context, objectives and constraints. What link can be established between safety culture and safety models in order to increase safety within companies carrying out dangerous activities? First, while the term "safety culture" is widely shared among the academic and industrial world, it leads to various interpretations and therefore different positioning when it comes to assess, improve or change it. Many safety theories, concepts, and models coexist today, being more or less appealing and/or directly useful to the industry. How, and based on which criteria, to choose from the available options? These are some of the questions addressed in this book, which benefits from the expertise of its worldwide famous authors in several industrial sectors. .
Preface, by Caroline Kamaté and François Daniellou -- An Industrial View on Safety Culture and Safety Models: What to Choose and How in the Nebulous "Safety Cloud" of Concepts and Tools?, by Olivier Guillaume, Nicolas Herchin, Christian Neveu, Philippe Noël -- Safety Models, Safety Cultures: What Link?, by Claude Gilbert -- Understanding Safety Culture Through Models and Metaphors, by Frank G. Guldenmund -- The Use and Abuse of "Culture", by Andrew Hopkins -- The Safety Culture Construct: Theory and Practice, by Dominic Cooper -- A Pluralist Approach to Safety Culture: Safety Cultures as Management Tools and as Professional Practices, by Benoît Journé -- Culture as Choice, by David Marx -- Safety, Model, Culture: the Visual Side of Safety, by Jean-Christophe Le Coze -- On the Importance of Culture for Safety: Bridging Modes of Operation in Adaptive Safety Management, by Gudela Grote -- Safety Culture and Models: "Regime Change", by Mathilde Bourrier -- Safety Culture in a Complex Mix of Safety Models: Are We Missing the Point?, by Corinne Bieder -- Key Issues in Understanding and Improving Safety Culture, by Stian Antonsen -- Safety Cultures in the Safety Management Landscape, by Jean Pariès -- The Commodification of Safety Culture and How to Escape It, by Hervé Laroche -- A Synthesis, by François Daniellou -- Afterword: A Number of Safety Models, Depending on their Intended Use, by René Amalberti.
Keywords: Security systems; Economic sociology; Psychology, Industrial; Industrial organization; Security Science and Technology; Economic Sociology; Work and Organizational Psychology; Industrial Organization